Propozycje leksykalne w „Łužiskim serbskim słowniku” K. B. Pfula – czasownik - Bura, Renata (Slavia Occidentalis, 2013)
The Łužiski serbski slownik by Křesćan Bohuwěr Pful originated as a result of the Sorbian national revival. As a revival dictionary, it presents a rich collection of words in which borrowings from other Slavic languages abound, accompanied by the dictionary author’s vocabulary proposals. Among other word forms, Pful suggested 95 verbs which reflect very diversified lexical resources with impressive word formations. Various derivatives have been identified with respect to the basis upon which they were formed, including adjectival, noun, verb, adverbial, pronoun and numeral as well as compound verbs. Some of the verb formations suggested by Pful have been incorporated into the lexical resources of Upper Sorbian.